ANALISIS DAN PERANCANGAN APLIKASI E-COMMERCE WEBSITE BUILDER BERBASIS WEB MENGGUNAKAN RESPONSIVE WEB DESIGN DAN CUSTOM FRAMEWORK (Jurnal Informatika dan Bisnis, 2016)
Information technology is currently growing very rapidly, especially in the Internet world that increasingly impact on all aspects of life, making people, especially entrepreneurs and aspiring entrepreneurs should be able to adapt to developments in the world of the Internet itself. One is in the area of sales also know as E-Commerce, we should be able to participate in these developments to contribute, and to exploit the opportunities. But the complexity of the design process and management, as well as the long time of making is becoming an issue that must be solved. And this is why this E-Commerce Website Builder is made for. This E-Commerce Website Builder itself is made with Multi-MVC custom framework which is adpoted from open source framework CodeIgniter and Bootstrap. This web application is also made with Responsive Web Design and Semantic HTML, and also has two section, a section for customer and for administrator. Â The collection of information is done by the method of direct observation and indirect observation. While the design methodology used in the development process is Waterfall methodology. Â This Web-based application provides many features for the creation and management of E-Commerce website such as user can create a new website with ease, administrators can control multiple websites at once, easy content management, print receipts and delivery sticker, etc. With the creation of this E-Commerce Website Builder the process of creation and management of the E-Commerce website will be easier, cheaper, and effective so that people, especially the people of Indonesia can also enliven in E-Commerce business.Keywords: Website Builder, E-Commerce Website Builder, Responsive Web Design, Custom FrameworkÂ